2020
DOI: 10.1038/s41597-020-0400-3
|View full text |Cite
|
Sign up to set email alerts
|

The sequence and de novo assembly of the wild yak genome

Abstract: Vulnerable populations of wild yak (Bos mutus), the wild ancestral species of domestic yak, survive in extremely cold, harsh and oxygen-poor regions of the Qinghai-tibetan Plateau (QtP) and adjacent high-altitude regions. In this study, we sequenced and assembled its genome de novo. In total, six different insert-size libraries were sequenced, and 662 Gb of clean data were generated. The assembled wild yak genome is 2.83 Gb in length, with an N50 contig size of 63.2 kb and a scaffold size of 16.3 Mb. BUSCO ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…The yak is a unique and rare ruminant living in the Qinghai–Tibet Plateau and adjacent regions. As an important livestock species for animal husbandry in this area, yaks provide local residents with agricultural products such as meat, milk, and hair while adapting to environmental conditions including cold, low oxygen, and high altitude and ultraviolet rays [ 16 , 17 ]. Because yaks graze year-round, their growth and development is restricted by the yield and quality of forage [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The yak is a unique and rare ruminant living in the Qinghai–Tibet Plateau and adjacent regions. As an important livestock species for animal husbandry in this area, yaks provide local residents with agricultural products such as meat, milk, and hair while adapting to environmental conditions including cold, low oxygen, and high altitude and ultraviolet rays [ 16 , 17 ]. Because yaks graze year-round, their growth and development is restricted by the yield and quality of forage [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Advances in sequencing technology over the past decade have provided novel insights into microbiome co-evolution and adaptability. Furthermore, herbivore adaptation mediated via the gut microbiota has attracted a great deal of research attention (Liu et al, 2020d ; Song et al, 2020 ; Fu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The domestic yak normally lives between 3000 and 5000 m above sea level while the wild yak, the ancestor of domestic yak, inhabits at elevations from 4000 to 6000 m on the QTP [1][2][3][4][5] . Archaeological and molecular evidences revealed that wild yak was domesticated at least 7300 years ago [6][7][8][9] . Although significant morphologic differences exist between wild and domestic yak 1 , both species share genetic features of high-altitude adaptation and are considered excellent models for studying hypoxia tolerance in large mammals.…”
mentioning
confidence: 99%
“…In 2012, the genome of a female domestic yak was sequenced using the Illumina-based whole-genome shotgun method 6 . In 2020, the genome of a female wild yak was assembled with the Illumina data 7 , and chromosome-scale genomes of female domestic yak were constructed using long-read sequencing and chromatin interaction technologies 10,11 . However, previous studies on yak have primarily focused on single nucleotide variants to reveal the genomic diversity and historical population dynamics 6,[12][13][14][15][16][17][18] .…”
mentioning
confidence: 99%